Aerobic & anaerobic capacity of trained swimmers in specific & non-specific exercises at the pre-competitive period - Vorontsov, A. R.; Solomatin, V. R.; Sidirov, N. N. (coachesinfo.com, 1998)
The growth of physical abilities and special working capability of swimmers at the level of training cycles has fluctuating character. Some papers [2,8,9] announced that specific motor abilities and functional power achieve their maximal level in swimmers 2-4 weeks before major competitions and they decline 10-15% by the day of competition. We did not find concrete data that supported these conclusions, and therefore decided to study functional capacity of trained swimmers at the pre-competitive period and to compare individual levels with corresponding levels of swimming achievements. Effective coaching controls individual parameters of motor abilities, functional power and working capability during different periods of the training season. Reliable methods to measure these parameters are also required [1,8,9,11]. The purposes of the present study were to: Investigate the levels of aerobic and anaerobic power and working capability of trained swimmers at the stage of taper before nationals. Compare physiological responses during a sub-maximal test in swimming flume and in cycling on veloergometer. Evaluate functional potential of swimmers in relation to competitive result.